2018
DOI: 10.3389/fneur.2017.00734
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor Cerebri and Glymphatic Dysfunction

Abstract: In contrast to virtually all organ systems of the body, the central nervous system was until recently believed to be devoid of a lymphatic system. The demonstration of a complex system of paravascular channels formed by the endfeet of astroglial cells ultimately draining into the venous sinuses has radically changed this idea. The system is subsidized by the recirculation of cerebrospinal fluid (CSF) through the brain parenchyma along paravascular spaces (PVSs) and by exchanges with the interstitial fluid (IF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
(103 reference statements)
2
31
0
2
Order By: Relevance
“…Other mechanisms that may cause neuroinflammation in the CNS are also possible. For instance, the “glymphatic system,” a functional metabolic waste clearance system that engages the CNS, can contribute to IH, and obstructions or flow disturbances can compromise the glymphatic system ( 27 ). Komaroff recently expressed this view of ME/CFS pathophysiology ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms that may cause neuroinflammation in the CNS are also possible. For instance, the “glymphatic system,” a functional metabolic waste clearance system that engages the CNS, can contribute to IH, and obstructions or flow disturbances can compromise the glymphatic system ( 27 ). Komaroff recently expressed this view of ME/CFS pathophysiology ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although transverse sinus diameter alone is not an adequate proxy for posterior fossa venous outflow, quantitative methods for measuring overall and segmental posterior fossa venous outflow are still not available. Numerous alternative pathways exist, including the occipital sinuses; occipital emissary veins; suboccipital venous plexus; a petrosquamous sinus; condylar veins and others that could play a role; as well as meningeal lymphatics and glymphatics, which are not visible at all with conventional imaging . A dynamic, flow‐based method that accounted for all possible alternative pathways would allow for systematic comparison between different cohorts of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous alternative pathways exist, including the occipital sinuses; occipital emissary veins; suboccipital venous plexus; a petrosquamous sinus; condylar veins and others that could play a role; as well as meningeal lymphatics and glymphatics, which are not visible at all with conventional imaging. [18][19][20] A dynamic, flow-based method that accounted for all possible alternative pathways would allow for systematic comparison between different cohorts of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Bezerra et al [100] proposed that the glymphatic dysfunction is identified as a major pathogenetic mechanism underpinning idiopathic intracranial hypertension.…”
Section: Conceptual Problems In Glymphatic Mechanisms Of Isf Transmentioning
confidence: 99%